Kinesiophobia, knee self-efficacy, and fear avoidance beliefs in people with acl injury: a systematic review and meta-analysis - Bullock, G. S.; Sell, T. C.; Zarega, R.; Reiter, C.; King, V.; Wrona, H.; Mills, N.; Ganderton, C.; Duhig, S.; Räisäsen, A.; Ledbetter, L.; Collins, G. S.; et al. (Sports Medicine, 2022)
Background: To improve the understanding of the psychological impacts of anterior cruciate ligament (ACL) injury, a systematic review synthesizing the evidence on knee self-efficacy, fear avoidance beliefs and kinesiophobia following ACL injury is needed. Objective: The aim of this systematic review was to investigate knee self-efficacy, fear avoidance beliefs and kinesiophobia following ACL injury, and compare these outcomes following management with rehabilitation alone, early and delayed ACL reconstruction (ACLR). Methods: Seven databases were searched from inception to April 14, 2022. Articles were included if they assessed Tampa Scale of Kinesiophobia (TSK), Knee Self-Efficacy Scale (KSES), or Fear Avoidance Beliefs Questionnaire (FABQ). Risk of bias (RoB) was assessed using domain-based RoB tools (ROBINS-1, RoB 2, RoBANS), and GRADE-assessed certainty of evidence. Random-effects meta-analyses pooled outcomes, stratified by time post-injury (pre-operative, 3-6months, 7-12months, > 1-2years, > 2-5years, > 5years). Results: Seventy-three studies (70% high RoB) were included (study outcomes: TSK: 55; KSES: 22; FABQ: 5). Meta-analysis demonstrated worse kinesiophobia and self-efficacy pre-operatively (pooled mean [95% CI], TSK-11: 23.8 [22.2-25.3]; KSES: 5.0 [4.4-5.5]) compared with 3-6months following ACLR (TSK-11: 19.6 [18.7-20.6]; KSES: 19.6 [18.6-20.6]). Meta-analysis suggests similar kinesiophobia > 3-6months following early ACLR (19.8 [4.9]) versus delayed ACLR (17.2 [5.0]). Only one study assessed outcomes comparing ACLR with rehabilitation only. Conclusions: Knee self-efficacy and kinesiophobia improved from pre-ACLR to 3-6months following ACLR, with similar outcomes after 6months. Since the overall evidence was weak, there is a need for high-quality observational and intervention studies focusing on psychological outcomes following ACL injury.